Changes of structural and techno-functional properties of high hydrostatic pressure (HHP) treated whey protein isolate over refrigerated storage. (February 2021) - Carullo, D.; Barbosa-Cánovas, G.V.; Ferrari, G.
Abstract: This work assessed the effect of storage time on the structure and functionality of HHP-treated whey protein isolate (WPI). Different pressures (100–600 MPa) and treatment times (15–30 min) were applied to aqueous WPI dispersions (5% w/v). The induced degree of unfolding was evaluated to select optimal HHP treatment conditions of WPI before storage at 4 °C. Conformational and techno-functional properties of untreated and optimally HHP-treated WPI samples were determined by UV–Vis and IR spectroscopy, foaming capacity, and interfacial tension measurements, respectively. Further tests of HHP-assisted hydrolysis of WPI were performed by α-chymotrypsin, bromelain, or their mixture (1:1 w/w), with the degree of hydrolysis (DH%) and electrophoretic patterns analyzed. The maximum unfolding degree was detected after a treatment of 400 MPa and 15 min and, at these processing conditions, no aggregation occurred. However, the structural changes achieved upon HHP were gradually lost during storage through a first-order refolding process (kREF. = 0.031 h −1 ), with restoring of native functionality. Hydrolysis performances of selected enzymes towards WPI were significantly promoted by high-pressure. Interestingly, a clear synergistic effect of α-chymotrypsin and bromelain combination on the WPI hydrolysis yield was detected, which resulted in the highest protein rupture (DH = 17%). Highlights: HHP treatment induced WPI unfolding and enhanced its interfacial properties. WPI pre-treated by HHP under optimal conditions underwent refolding and loss of functionality during refrigerated storage. HHP dramatically improved the enzymatic hydrolysis of WPI. Combining α-chymotrypsin and bromelain resulted in a synergistic effect on the degree of hydrolysis of WPI.